A Comparison of Texts for Writing and Original Speaking Texts by Correspondence Analysis - Uenishi, Koji (Advances in Social Sciences Research Journal, 2022)
This paper explores the differences of the four texts used in speaking and writing classes. Specifically, the texts were analyzed using a readability tool and Correspondence Analysis (hereafter, CA). An analysis of the data suggests that, in terms of readability and content, there were both similarities and differences among the four texts. More precisely, regarding readability, the two texts for the speaking class are closer to the level of English textbooks which junior high school students (seniors) use, compared to the other two texts. In addition, concerning the content including vocabulary, CA shows that the two texts, Writing 1 and Writing 2, are similar to each other, but those texts are different from the other two texts, Speaking 1 and Speaking 2.